The impact of insect herbivory on biogeochemical cycling in broadleaved forests varies with temperature - Hwang, Bernice C; Giardina, Christian P; Adu-Bredu, Stephen; Barrios-Garcia, M Noelia; Calvo-Alvarado, Julio C; Dargie, Greta C; Diao, Haoyu; Duboscq-Carra, Virginia G; Hemp, Andreas; Hemp, Claudia; Huasco, Walter Huaraca; Ivanov, Aleksandr V; et al. (Nature communications, 2024)
Herbivorous insects alter biogeochemical cycling within forests, but the magnitude of these impacts, their global variation, and drivers of this variation remain poorly understood. To address this knowledge gap and help improve biogeochemical models, we established a global network of 74 plots within 40 mature, undisturbed broadleaved forests. We analyzed freshly senesced and green leaves for carbon, nitrogen, phosphorus and silica concentrations, foliar production and herbivory, and stand-level nutrient fluxes. We show more nutrient release by insect herbivores at non-outbreak levels in tropical forests than temperate and boreal forests, that these fluxes increase strongly with mean annual temperature, and that they exceed atmospheric deposition inputs in some localities. Thus, background levels of insect herbivory are sufficiently large to both alter ecosystem element cycling and influence terrestrial carbon cycling. Further, climate can affect interactions between natural populations of plants and herbivores with important consequences for global biogeochemical cycles across broadleaved forests.
Keywords: Plant Leaves; Trees; hmyz; Nitrogen; dusík; Temperature; Forests; Ecosystem; lesy; fosfor; stromy; Carbon Cycle; teplota; zvířata; listy rostlin; býložravci; Insecta; Herbivory; Carbon; Phosphorus; koloběh uhlíku; Animals; uhlík; ekosystém